KDC Based KP-ABE for Data Encryption in Cloud - Lathwal, Reenu; Saroha, Vinod Kumar (International Journal of Computer Sciences and Engineering, 2015)
There are lots of cipher-text policies to provide control access mechanism. Attribute-based encryption reconsiders the concept of public-key encryption in which the secret key of a user and the ciphertext are dependent upon attributes. In this, the decryption of a ciphertext is possible if the set of attributes of the user key matches the attributes of the ciphertext. File distribution and sharing is the most commonly used services in the cloud computing. Attribute based encryption is the attractive way to manage and control file sharing in cloud with its special attribute computing properties. Attribute-based encryption (ABE) is a new cryptographic primitive which provides a promising tool for addressing the problem of secure and fine-grained data sharing and decentralized access control. The authors take a centralized approach where a key distribution center (KDC) distributes secret keys and attributes to all users. Cloud computing is a new concept of computing technique, by which computer resources are provided dynamically via internet. Decentralized scheme also has the added feature of access control in which only valid users are able to decrypt the stored information. The scheme supports creation, modification, and reading the data stored in cloud and also provide the decentralized authentication and robust. It can be comparable to centralized schemes for the communication of data, computation of data, and storage of data.